An Unusual Presentation of Congenital Lobar Emphysema - Daniel Arnaud; Joseph Varon; Salim Surani (Case Reports in Pulmonology)
Congenital lobar emphysema is an uncommon bronchopulmonary malformation characterized by lobar overinflation and accompanying alveolar septum damage that leads to compression atelectasis of the lung parenchyma and displacement of mediastinal structures, with the resultant ventilation-perfusion mismatch. We present a case of a 33-year-old lady with progressive exertional dyspnea. Chest radiograph findings lead to the suspicion of congenital lobar emphysema, which was then confirmed by a computed tomography (CT) scan. This condition is most commonly identified in newborns, with very few cases being reported in adults. Lobectomy remains the treatment of choice and in general has good outcome.